(Evaluation of the relationship between the search habits of the consumers and companies use of SEO as a strategy for electronic marketing (applied to the Saudi market - Fayed, Abeer Elsayed (Journal of Economic, Administrative and Legal Sciences, 2018)
The current study aimed to investigate the problem of non-exploitation of Saudi sites for the habits of consumers in the search for products, which is the search through the free search engines (known as the strategy of search engine optimization), which is the preferred strategy of most consumers, and the result of this problem in the ineffectiveness of e-marketing strategies used In the Saudi market, and this was a strong phenomenon worthy of study and identify the causes. The study was based on the analytical descriptive method with the distribution of a questionnaire to collect the primary data, and then the analysis of these data statistically, using some statistical methods used in the SPSS program. The study showed that the Saudi sites and products did not appear to the consumers when they searched for the products in the way they prefer. They search through the free search engines. The appearance of the products requires the search engines to prepare their sites to appear in the first results of the search results, otherwise they become ineffective. This is what Saudi sites have overlooked and have not implemented. The study also found that the reason why the e-marketing strategies are ineffective is that they do not give consumers confidence and confidence about the products. They do not promote them. They do not educate consumers about Saudi products. They do not use the preferred marketing strategies of consumers. Consumers of the Saudi market, and finally because it overlooked the steps to implement the strategy of the formation of search engines, and to address all these reasons lies in the use of the strategy of the formation of search engines. This is what Saudi sites do in practice. The study recommended the adoption of companies on the strategy of creating the search engines as a preferred strategy for the users in e-shopping, and also recommended the need to follow the conditions constantly updated by the search engines, and not follow any methods that lead to deletion or even appearing in the latest results of the search as a fake links.